Tradisi Bakar Tongkang dalam Memperkuat Civic Culture Masyarakat Adat di Bagan Siapiapi - Elzenia, Alia Dwi; Salfira, Belsa; Nasution, Dita Maisaroh; Mursyid, Ekmal; Putri, Nabila Ananda; Jelita, Nadely Syarrova; Athifa, Naela; Tahmi, Tamala; Yuliana, Yuliana; Hambali, Hambali (Pancasila and Civics Education Journal (PCEJ), 2025)
ABSTRACTThe Bakar Tongkang tradition in Bagan Siapiapi, Riau, is not only a cultural asset, but also functions as a strategic tool in strengthening civic culture in the midst of a multi- ethnic indigenous community. This study uses a qualitative method with a literature study approach to analyze the role of tradition in fostering values of solidarity, public participation, and cross-ethnic cooperation. The results of the study reveal that this ritual has succeeded in building a shared identity and strengthening social ties through community involvement in the preparation to implementation stages, driven by local government policies. However, threats such as the dominance of commercial aspects, low involvement of the younger generation, and environmental issues have the potential to erode the sustainability of tradition. To overcome this, solutions such as incorporating traditional values into the education system, utilizing digital technology, and synergy between related parties are considered crucial. This study confirms that Bakar Tongkang can remain the foundation of civic culture by maintaining a balance between preservation and renewal, while ensuring its sustainability amidst global dynamics.Keywords: Bakar Tongkang; Civic Culture; Indigenous Peoples ABSTRAKTradisi Bakar Tongkang di Bagan Siapiapi, Riau, tidak sekadar menjadi aset budaya, melainkan juga berfungsi sebagai alat strategis dalam memperkuat civic culture di tengah masyarakat adat yang multietnis. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur untuk menganalisis peran tradisi dalam menumbuhkan nilai solidaritas, partisipasi publik, dan kerja sama lintas etnis. Hasil kajian mengungkap bahwa ritual ini berhasil membangun identitas bersama dan mempererat ikatan sosial melalui pelibatan masyarakat dalam tahap persiapan hingga pelaksanaan, didorong oleh kebijakan pemerintah setempat. Namun, ancaman seperti dominasi aspek komersial, rendahnya keterlibatan generasi muda, serta persoalan lingkungan berpotensi mengikis kelestarian tradisi. Untuk mengatasinya, solusi seperti memasukkan nilai tradisi ke dalam sistem pendidikan, memanfaatkan teknologi digital, dan sinergi antar pihak terkait dinilai krusial. Penelitian ini menegaskan bahwa Bakar Tongkang dapat tetap menjadi fondasi civic culture dengan menjaga keseimbangan antara pelestarian dan pembaruan, sekaligus memastikan keberlanjutannya di tengah dinamika global.Kata Kunci: Bakar Tongkang; Civic Culture; Masyarakat Adat